Correlation between clinical severity and quality of life in moderate to severe psoriasis patients: real-world evidence - Milidrag, Ardea; Safiye, Teodora; Gutić, Medo; Zlatanović, Milena; Radević, Svetlana; Ravić-Nikolić, Ana (Vojnosanitetski pregled, 2023)
Background/Aim. Psoriasis is a chronic multisystem, inflammatory, and immune-mediated dermatological disease of a relapsing nature. Not only does it affect objective parameters such as skin and joints, with different intensity involvement and with changes and the degree of changes, but it also significantly affects the health-related quality of life (QoL). The aim of the study was to determine the clinical severity and QoL of patients with moderate to severe psoriasis and examine the association between those parameters before and after the treatment. Methods. This cross-sectional study included 183 patients diagnosed with moderate to severe psoriasis. The severity of the clinical picture was determined by calculating the Psoriasis Area and Severity Index (PASI) by a dermatologist, while the QoL was assessed using the Dermatology Life Quality Index (DLQI) questionnaire and psoriasis-related stress by the Psoriasis Life Stress Inventory (PLSI). Disease severity and QoL were measured at the baseline visit and after the 16th week of therapy. Results. The average PASI score at the beginning of therapy was 23.1 ± 6.5, while after 16 weeks, this value was 4.36 ± 4.86. The DLQI score was 20.8 ± 5.0 at the start of therapy and 6.20 ± 6.16 after 16 weeks, while the PLSI score was 35.37 ± 8.84 initially and 12.75 ± 12.82 after 16 weeks of therapy. A strong correlation was found between PASI and PLSI scores (r = 0.702, р < 0.001) in the 16th week of therapy, while the correlation between DLQI and PASI scores was moderate (r = 0.683, р < 0.001). No significant differences between PASI and DLQI scores were found (r = 0.080, р = 0.284) nor between PASI and PLSI scores (r = 0.109, р = 0.140) at baseline. Conclusion. Patients with severe psoriasis experience a significant reduction in their QoL, accompanied by a high level of psychosocial stress. Observed improvements in QoL have shown a moderate correlation, while lower levels of psychosocial stress have strongly correlated with the severity of the clinical presentation, which may indicate a complex interaction between psychological factors and physical health in patients with psoriasis.
Keywords: psoriasis; quality of life; severity of illness index; surveys and questionnaires; stress, psychological